Central Neuraxial Blockade-Assisted External Cephalic Version in Reducing Caesarean Section Rate: Systematic Review and Meta-Analysis - Ibrahim Bolaji; Lillian Alabi-Isama (Obstetrics and Gynecology International)
We review the medical literature on the success, safety and economic value of central neuraxial blockade-assisted (CNB) external cephalic version from randomized controlled studies identified from 1951 to 2009. The result showed that more women had successful ECV with regional anaesthesia with corresponding reduction in caesarean section rate. They were 1.5 times more likely than women not receiving anaesthesia to have a successful ECV. The number to treat is six women needed to receive anaesthesia for 1 baby to be turned from breech to cephalic presentation. Feto-maternal morbidity was not increased in the CNB-aided group consisting of only transient bradycardia. Although the appropriate amount of force for safe version has not been quantified, there was no report of uterine rupture despite removal of these patients from “excessive force-pain biofeedback loop” induced through motor nerve blockade. We can attribute 30% of cost savings amounting to £42,150.00 directly to CNB using the most up to date Health Resource Group Code (HRG4). The initial results are encouraging but until the benefits and safety of CNB-aided ECV are substantiated by large randomized, blinded controlled trials, this practice cannot be universally recommended.